An Efficient Approach for Stimulating Cooperation among Nodes in Wireless Sensor Networks. (26th May 2016) - Xu, Hongyun; Wang, Ding; Shen, Shigen; Shi, Youqun; Cao, Qiying
Abstract : A Wireless Sensor Network (WSN), characterized as being self-organizing and multihop, consists of a large number of low-power and low-cost nodes. The cooperation among nodes is the foundation for WSNs to achieve the desired functionalities, such as the delivery or forwarding of packets. However, due to the limited resources such as energy, computational availability, and communication capabilities, there may exist some selfish nodes that refuse to cooperate with others. If the critical masses of nodes do not cooperate in the network, the network would not be able to operate to achieve its functional requirements. To resolve the problem above, we introduce a Win-Stay, Lose-Likely-Shift (WSLLS) approach into a Prisoner's Dilemma (PD) game framework, and it applies a utility-based function, which is a linear combination of one player's payoff and its neighbors' in a game, to evaluate a player's (i.e., node) performance for a game. Experimental results demonstrate that our approach performs well in stimulating cooperation in different settings under a certain condition with limited information, regardless of the static topologies types of WSNs, initial proportion of cooperation, and the average number of neighbors.